2018
DOI: 10.1016/j.pec.2018.05.026
|View full text |Cite
|
Sign up to set email alerts
|

A rigorous evaluation of an institutionally-based communication skills program for post-graduate oncology trainees

Abstract: Objective: Integrating education about physician-patient communication into oncology specialists’ education is important to improve quality of care. Our aim was to rigorously evaluate a 4-year institutionally-based patient communication skills program for oncology post-graduate trainees. Methods: Trainees from 10 specialties in the U.S. participated in patient communication skills modules tailored to sub-specialties. The program was evaluated by comparing pre-post scores on hierarchical outcomes: course eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 30 publications
2
48
0
Order By: Relevance
“…In this study, significant SEGUE score increases were found both immediately after programme (OR = 7.017, p < 0.001) and 1 month after programme (OR = 11.716, p < 0.001) for trainees with lower baseline scores. This finding was in line with a previous study by Bylund et al [18]. They also found that participants with lower baseline scores had larger improvements with both standardized and real patients.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, significant SEGUE score increases were found both immediately after programme (OR = 7.017, p < 0.001) and 1 month after programme (OR = 11.716, p < 0.001) for trainees with lower baseline scores. This finding was in line with a previous study by Bylund et al [18]. They also found that participants with lower baseline scores had larger improvements with both standardized and real patients.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, in the development process of the training concepts it should be taken into account, that different skills/domains may need different intensity of work to be changed, probably dependent on the prior knowledge/skills of the physician. A study by Bylund and colleagues [ 40 ] describes, for example, that although no transfer was observed in the trained physicians as a whole, the subgroup of the weaker physicians at baseline showed significant changes on their communicative behavior. Here also arises a further challenge for future research: only a better understanding of the learning processes [ 44 ] and the learning context [ 39 , 45 ] of the physicians will allow an enhancement of the training methods.…”
Section: Discussionmentioning
confidence: 99%
“…A crucial question remains how to transfer skills into clinical practice [ 39 ]. Studies have shown that the effects of the training are minor when assessed with real patients and do not last long, the effect disappearing after no later than one year [ 2 , 7 , 34 , 40 ]. This problem of low transfer despite intensive work is known from Organization Psychology [ 41 ] and has triggered significant research, the aim of which is to better understand how transfer works and identify which factors support or disturb this process [ 25 , 42 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Kirkpatrick Assessment Model's application to communication skills education programs has been found to be a good fit. 17 The model does not explicitly consider the length of time that has passed in its evaluation levels, although it is somewhat implicit, particularly at the highest level. In other words, the highest level of "result" may take some time to become apparent.…”
mentioning
confidence: 99%
“…Conventional wisdom among healthcare communication educators is that learned skills drop off over time, but there are few data to support this, with only a few studies that show mixed results. 17,[19][20][21] We considered whether an innovative and feasible approach to gaining some insight into the long-term effect of the course would be to conduct a cross-sectional study of participants who had completed a communication skills course at varying times (6-36 months ago) to assess the long-term effect at the third level of the Kirkpatrick modelbehavior. Specifically, we wanted to examine whether time since course completion was related to reported use of communication skills learned in the course, allowing for a snapshot of the effect of communication skills education on doctors' behavior over time.…”
mentioning
confidence: 99%